Normocalcemic Primary Hyperparathyroidism in Adults Without a History of Nephrolithiasis or Fractures: A Prospective Study - Rosário, Pedro Weslley; Calsolari, Maria Regina (Hormone and Metabolic Research, 2019)
The prevalence and the diagnostic criterion of “normocalcemic” primary hyperparathyroidism (NPHPT) are still uncertain and there is no consensual definition. This prospective study evaluated the prevalence of NPHPT in 676 adults without a history of fractures or nephrolithiasis and who would be submitted to thyroidectomy, the impact of adopting different cut-off values for 25-hydroxyvitamin D and estimated glomerular filtration rate (eGFR), and the agreement between biochemical diagnosis and the surgical finding of altered parathyroid glands. NPHPT was diagnosed in patients with normal total and ionized calcium and elevated PTH (in 2 measurements) and without a known cause of secondary HPT, including eGFR<40 ml/min/1.73 m2 and 25-hydroxyvitamin D<20 ng/dl. The 4 parathyroid glands were fully explored in these patients. Forty-six patients (6.8%) had a laboratory diagnosis of NPHPT. Altered parathyroid glands were detected in only 4 patients, corresponding to 0.6% of all patients and to 8.7% of those with a biochemical diagnosis of NPHPT. The latter was confirmed in 0/174 men, 1/252 premenopausal women, and 3/250 postmenopausal women. Among the 42 patients with elevated PTH and without altered parathyroid glands, 25 had 25-hydroxyvitamin D between 20 and 30 ng/dl, 7 had eGFR between 40 and 60 ml/min/1.73 m2, and 9 had both. The prevalence of NPHPT was 0.74% in this adult population without a history of nephrolithiasis or fractures. The diagnostic criterion using eGFR>60 ml/min/1.73 m2 and 25-hydroxyvitamin D>30 ng/dl was more appropriate considering the agreement with the surgical finding of altered parathyroid glands.
Keywords: primary hyperparathyroidism; normocalcemic; secondary hyperparathyroidism; diagnosis; prevalence